TEACHERS’ PERCEPTIONS OF GRAMMARLY FOR WRITING ASSESSMENT: QUANTITATIVE STUDY - Damashola, Alfina; Sulistyanto, Irwan; Prasongko, Angga (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2025)
In the era of globalization, proficiency in English writing has become a crucial skill for academic and professional success. Digital tools such as Grammarly have emerged as valuable aids in enhancing teachers’ writing assessment accuracy and quality. This study explores English teachers’ perceptions of Grammarly as a writing assessment tool at a Public High School. Employing a quantitative descriptive research design, data were collected from English teachers through a structured questionnaire using a Likert scale. The study examines four key indicators: effectiveness, usability, limitations, and challenges. The findings reveal that teachers generally perceive Grammarly as an effective and user-friendly tool for writing assessments. However, they also recognize its limitations and challenges, particularly in areas such as contextual accuracy and teacher dependency on automated corrections. The results provide significant insights into the role of AI-based writing tools in educational settings and offer recommendations for their optimal integration into writing instruction and assessment.